Predicting children’s prosocial skills in the early school years: The role of toddler emotional and attentional regulation and parenting - Williams, Kate; Williams, Kate E; Berthelsen, Donna (My University, 2016)
This study uses data from Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC) and longitudinal modelling to investigate how positive parenting contributes to the development of enhanced toddler self-regulatory skills and subsequently enhanced prosocial behaviour of young children.
Keywords: Families -- Parents and Parenting; Child Development; Children -- Early childhood; Childhood and child development; Families and relationships; Children; Child Development; Families; Parents and Parenting; Early childhood; Families and relationships; Childhood and child development